Analysis of Digital Potential Development Factors for Enterpreneurs in the Z Generation - Nurul Azizah; Siti Ning Farida; Dyah Widowati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Measurement of achievement in three main areas conducted by PISA (Program for Entrepreneurship Level in Indonesia is still relatively low compared to other countries. The role of entrepreneurs is very important for strengthening a country's economy. The potential of the dominant generation Z in the next few years must be prepared as early as possible to be ready to become entrepreneurs. However, not many young people or students have a strong desire to become entrepreneurs. Especially among students. Students are a potential age group and have great potential in starting or developing an entrepreneurial spirit. So, it is necessary to understand how to see the entrepreneurial potential of students. Entrepreneurial potential will be greatly influenced by a person's motivation. A person's motivation is greatly influenced by internal and external factors. Internal motivation is everything related to the individual, including: feeling the need for personal challenges, self-esteem, and the desire to lead. External motivation is everything that grows from factors outside the individual, such as the school environment, education, and family environment. External motivation in this study consists of entrepreneurship education, basic knowledge of entrepreneurship, and perceptions of social support. The sample in this study was taken from Generation Z from various regions who were pursuing higher education in Surabaya, to support the strengthening of the Indonesian economy in the future. The method used in this study is a quantitative approach. The research instrument used was a questionnaire, which would then be tested descriptively and inferentially using SmartPLS software. The results of the data test showed that external motivation, which in this study included entrepreneurship education, basic knowledge of entrepreneurship, and perception of social support, influenced digital entrepreneurship interest. Then on internal motivation, which includes personal challenges, self-esteem, and the desire to lead, influences digital entrepreneurship interest in Generation Z.